Limitovaný versus extenzivní laterální přístup při osteosyntéze zlomenin patní kosti – srovnání časových a dynamických parametrů krokového cyklu - Jandová, Soňa; Pazour, Jan (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2018)
PURPOSE OF THE STUDY Currently, operative treatment is preferred in dislocated calcaneal fractures. Most frequently used is the extended lateral approach, the disadvantage of which is the risk of early complications. Therefore, less invasive operative techniques are sought that would reduce the risk of such complications. The presented study aimed to compare the two different surgical approaches with respect to the restoration of gait stereotype using the objective pedobarography. We assume that the limited operative approach in osteosynthesis of intra-articular calcaneal fractures results in comparable or earlier restoration of gait stereotype with regard to temporal and dynamic parameters compared to the extended lateral approach. MATERIAL AND METHODS The research study comprised a total of 22 patients who underwent the surgical treatment of intra-articular calcaneal fractures, divided into two groups by the applied operative approach. The first group consisted of 10 patients treated with less invasive sinus tarsi operative approach (ST). For osteosynthesis a calcaneal nail (C-nail, Medin, CR) was used. The second group consisted of 12 patients, to whom extended lateral approach (EXT) was applied. For osteosynthesis a calcaneal plate 3.5 mm (DePuy Synthes, Switzerland) was used. Pedobarographic measurement using a tensometric platform was performed in all the patients, always six months post-operatively. Temporal and dynamic variables of the gait cycle during the interaction of the foot with the ground were monitored. RESULTS In the EXT group, significant differences between the injured and healthy foot were found in walking 6 months after the surgery in most of temporal and dynamic variables. The ST group, however, showed no significant differences between the values for the injured and healthy foot in most of temporal and dynamic variables. DISCUSSION Six months after the surgery, the patients continue to carefully load the heel, regardless of the selected surgical approach, due to which the pressure at this place is significantly reduced and tends to be transferred to the midfoot or forefoot. This finding corresponds with previous studies. The patients undergoing a less invasive surgical approach load both the operated and healthy feet. Also, with regards to temporal parameters, as early as 6 months after the surgery correct gait stereotype is restored under the heel in these patients. We believe this is achieved thanks to less pain due to a limited extent of the surgical approach. On the very contrary, the extended lateral approach can cause deterioration of conditions for the restoration of gait stereotype due to the presence of extensive scarring on the heel side with a limited mobility of talocalcaneal joint or also an impaired mobility of peroneal tendons outside the ankle bone. CONCLUSIONS Six months after the surgical treatment of calcaneal fractures changes still persist in gait stereotype. The analysis of temporal and dynamic gait parameters in the followed-up group of patients reveals that the limited sinus tarsisurgical approach results in an earlier restoration of gait stereotype compared to the extended lateral approach. A higher number of patients in the respective groups is necessary in order to obtain more general results. Key words:sinus tarsi; extended lateral approach; plantar pressure; force; contact time.
Keywords: Calcaneus; dospělí; fraktury kostí; subtalární kloub; Female; Postoperative Period; Adult; Gait; kostní hřeby; ženské pohlaví; lidé; hodnocení výsledků zdravotní péče; Fractures, Bone; intraartikulární fraktury; Subtalar Joint; pooperační období; patní kost; Bone Plates; kostní destičky; Bone Nails; Male; Intra-Articular Fractures; vnitřní fixace fraktury; lidé středního věku; mužské pohlaví; chůze (způsob); Middle Aged; Fracture Fixation, Internal; Outcome Assessment, Health Care; Humans